Outdoor Learning With Outbond Variations 21st Century Social Studies Learning Alternative - Maesaroh Maesaroh; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2022)
Social studies learning process has not been implemented optimally. The application of the Outbound variation of the Outdoor Learning method as a solution to this problem . The instrument used was an observation sheet for student creativity and collaboration. The implementation of learning using an outdoor learning strategy with outbound variations is carried out optimally with very good criteria. The application of this method is carried out by inviting students to study outside the classroom (out door learning) to increase student creativity and collaboration in a pleasant learning atmosphere. The outdoor learning approach (outdoor learning) of outbound variations for children is very useful, it is a learning program (training) for children carried out in the open based on the principle of "experimental learning" (learning through direct experience) which is presented in the form of games, stimulus, discussion and adventure as a medium for delivering material. This outbound learning aims to overcome the problems of children who lack motivation in learning activities, improve children's self-competence, develop abilities and creative ideas. The 21st century learning model includes: first, learning is directed at encouraging students to find out from various sources, not being told. Second, learning is directed to be able to formulate problems or ask questions, not just solve problems or answer. Third, learning is directed at training analytical thinking, as in the case of the decision-making process, not mechanistic and routine thinking. Fourth, learning emphasizes the importance of cooperation and collaboration in solving problems.